Propuesta de un sistema de gestión por procesos para la unidad de control ambiental del ilustre municipio del cantón Salcedo. - González Vargas, Pilar Del Rosario (2012)
The proposal of a management system by process for the unit of control environmental of the llustrious Municipality of the Canton Salcedo has as objective main improve the actual situation of the processes with the "Propose a system of management by process for the unit of control environmental." The first chapter presents information and activities performed in this unit that allowed identify problems, and was determined hypothesis and objectives of the project. The second chapter explains and samples the concept of all guides and guidelines that were used in the realization of the project as: process management, process maps, process flows, management indicators, manual process. The third chapter is a description of the methodology, methods, techniques and procedures for the elaboration of a management system by process. The fourth chapter is the analysis and interpretation of the results, based on the diagnostic of the actual situation. In the fifth chapter develops the proposal of improves with regard to strategic addressing, the definition of processes flow diagrams of the actual situation, we determined the processes with greater contribution to the objectives of the organization, and analyzes through a matrix of aggregate value, is proposed improvements to decrease the effective times of process cycles making them more efficient. We present improved flow diagrams, management indicators. Besides of conclusions and recommendations.